Placenta accreta not previa: a rare case report of placenta accreta in an unscarred uterus - Malik, Renuka; Singh, Swati; Chawla, Jaya; Bhardwaj, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Placenta accreta spectrum disorders are usually associated with direct surgical scar such as caesarean delivery, surgical termination of pregnancy, Dilatation and curettage, Myomectomy, Endometrial resection and Asherman’s syndrome. It can also be associated with non-surgical scar and uterine anomalies. Rarely it can be encountered in unscarred uterus. Mrs X, 35-year female, unbooked patient, G7P2L2A4 with nine months of amenorrhoea reported in emergency of RML Hospital on 30/07/2019 with history of labour pains since 2 days. Patient gave history of four dilatation and curettage for incomplete abortion. On examination patient was found to be severely anaemic (Hb -6 gm). 2 Packed RBC were transfused preoperatively. There was no progress in labour beyond 6 cm for 4 hours. Patient was thus taken for LSCS for NPOL, with blood on flow. Intraoperatively, after delivery of the baby placenta which was fundo-posterior did not separate. In view of parity and morbidly adherent placenta (clinical grade III), subtotal hysterectomy was done. Patient was transfused 4 PRBC, 4 FFP and 2 platelets. Uterus with placenta in situ was sent for histopathology. Patient was in ICU for 2 days and recovered well. Post-operative period was uneventful. Placenta accreta is defined as abnormal trophoblast invasion of whole or a part of placenta into myometrium of uterine wall. Caesarean delivery is associated with increased risk of placenta accrete and the risk increases with each caesarean section, from 0.3% in woman with one previous caesarean delivery to 6.47% for woman with five or more caesarean deliveries. Placenta accreta spectrum disorders occur in 3% of woman diagnosed with placenta previa and no prior caesarean. In the developing world, the obstetrician should be prepared to encounter un diagnosed placenta accrete even in absence of previous LSCS. Curretage following MTP is also a risk factor, so vigourous currettage should be avoided to prevent endometrial damage.